Estilo de ocorrência de minerais portadores de ETRs no Albita Granito da Suíte Madeira: Pitinga, AM - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Minerals bearers of elements of the rare (ETRs) lands in Albita Granite of Nucleus of the plúton Wood (mine of Pitinga) they were studied using analytical techniques for DRX, MEV and petrografica, having been accomplished structural geological mapping of the digging of the mine with the intention of evaluating the space distribution and structural control on the occurrence of dikes pegmatites and veins with fluorita. The analyses petrográficas were accomplished seeking to understand the mineral association and the processes put upon as deformation and/or alteration hydrothermal. Analyze them of diffraction of rays X (DRX) accomplished in the affected granite by process hydrothermal, that modified the texture and composition of the rock, to identify mineral argilo and minerals related to the event hydrothermal and with occurrence of elements rare (ETR) lands, and transition (ítrio) elements. The focus of the research consists of determining the style of occurrence of the minerals bearers of ETR and transition elements and the related minerals associations the these to understand the processes formators and to postulate a model that explains the presence of these minerals in the granite. The results of the research showed that mine accessory common in granites as zircon, apatite are accompanied of exotic minerals as, cryolite, xenotime, torite, riebeckite, pyrochlore and polilitionite, mainly of origin magmatic and late derived magmatic of the crystallization of two pulses discreet granitic, registering structure in banding compositional of flow magmatic that controls the space distribution of these mines, that exhibit organization and they link with minerals albita, K-feldspar and quartz, deformed for mechanisms developed in high temperature. Fluid late magmatic formed dikes with texture pegmatite and composition granitic, whose minerals associate to zircon, criolita, xenotime, genthelvita, riebeckite, epidote, pyrochlore, gagarinite, polilitionite. It increases that happened later Pulse of fluids constituted by cassiterite, torite and oxides of iron. And pulses constituted by fluorite, allanite, fluocerite, chlorite and galena forming veins. Dikes and veins spatially present pattern of compatible orientation with model of shearing guided dextral 260° and close dive of 60° for associated N her conjugated synthetic with attitude dominant close 110° dive of 70° for S and the structure tensile with close attitude of 340° and I dip subvertical for W. This model controlled the placement of the pluton, and the development of structures with occurrence of the minerals bearers of ETRs. The fluids rich hydrothermal in ETR percolated the albite granite and they generated argilo mineral product of the alteration of the same. The structural pattern and the identified mineral association, they attest the coherence with that the minerals bearers of ETRs are distributed in the albite nucleus granite.
Keywords: Minerais exóticos; Xenotima; Gagarinita; Granito Madeira; Distrito minero de Pitinga; CIÊNCIAS EXATAS E DA TERRA: GEOCIÊNCIAS